MAKNA VERBA ‘MEMASAK’ BAHASA BALI: PENDEKATAN METABAHASA SEMANTIK ALAMI - I Nengah Sudipa (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
This article aims at mapping the meaning configuration  of Balinese verb belonging to the concept of cooking. The data was taken from spoken Balinese and collected by direct observation and participation combined with note-taking. The collected data was analyzed by applying the theory of Natural Semantic Metalanguage. The result showed that there are a number f lexicons showing such a promising concept: ngangetin, ngoréng/ngenyahnyah, nguling, nyakan: (nguskus, nepeng), ngelablab/nadah nunu, manggang, nambus, nimbung. It turns out that the slight difference between nunu and manggang can be explicated. The other findings showed that – through NSM – the subtypes of nyakan can be mapped into ngu(s)kus and nepeng, and the variants of ngoréng is ngenya(h)nyah, and ngela(b)lab is nada.